Implementasi Gamification Learning menggunakan Aplikasi Kahoot! pada Mata Pelajaran Instalasi Penerangan Listrik - Farhan, M.; Yanto, Doni Tri Putra (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
In the Electrical Lighting Installation course, student learning outcomes were found to be below the Minimum Completeness Criteria (KKM). Several factors contributed to this issue, including students’ limited understanding of tools and materials as well as their low engagement during learning activities. Therefore, it is essential to adopt an instructional approach that aligns with students’ interests to enhance motivation and participation. Gamified learning using the “Kahoot!” application represents one such approach that can effectively address these challenges. This study employed a quasi-experimental design involving two groups: a control group and an experimental group. The experimental group received treatment through the implementation of gamified learning with “Kahoot!”, while the control group was taught using conventional methods. The research design used was a pretest–posttest non-equivalent control group design, suitable when random assignment of participants is not feasible. The study involved 25 students from class XI TITL 1 (experimental) and 29 students from class XI TITL 2 (control) at SMK Negeri 5 Padang. Data were collected through pretests and posttests to measure students’ cognitive learning outcomes before and after the intervention. The results indicated a significant improvement in the experimental group’s learning outcomes compared to the control group. Furthermore, the use of Kahoot! enhanced students’ activeness and engagement during learning activities. These findings demonstrate that the integration of gamified learning through Kahoot! is not only feasible for vocational education but also effective in creating an interactive and motivational learning environment that promotes the achievement of student competencies.